Legal regulation of the statutory matrimonial regime in Russia and Bulgaria: a comparative legal aspect - T. A. Filippova; E. P. Titarenko; A. V. Korneeva (Правоприменение)
The subject of the study is the legislation of the Russian Federation and the Republic of Bulgaria, in particular, the Family Codes of these states, devoted to the regulation of issues of the legal regime of the property of the spouses as well as the law enforcement practice.The objective is aimed at confirming the scientific hypothesis that the RF Family Code does not fully take into account the processes of globalization taking place in the modern world, changes in the economic sphere, the development of digital technologies. It is supposed to confirm the scientific hypothesis about the possibility of improving Russian family legislation, taking into account the experience and practice of foreign countries, primarily those having similar legal systems, common language groups, belonging to one world religion, having geographical proximity, social communities proximity as well as the ability to exchange information and orientation to the preservation of traditional family values.Research methods. The use of the method of comparative analysis made it possible to study the national legislation of Russia and Bulgaria and identify the general trends in its formation into the regime of joint property of the spouses. Main results. This study has allowed us to confirm the conclusion that there are unresolved issues in Russian legislation, gaps related to the legal regime of property of the spouses, which give rise to controversial practice. There is a need to establish new legislative rules in the RF Family Code that meet the development trends of modern society and take into account modern realities. The analysis of Bulgarian legislation and the practice of its application have shown that the legislation of Bulgaria contains a number of provisions, to a greater extent than the Russian one, that take into account the interests of the family, minor children, former spouses when establishing matrimonial property regimes.